Parental assessment of communication attitudes in children with stuttering in early school age – practical implications - Radkowska-Marczak, Natalia (Logopedia Silesiana, 2024)
The article presents a quantitative study of how parents assess the communication attitudes of early school-age children who stutter compared to parents of fluent-speaking peers, using a questionnaire adapted from the Communication Attitude Test (CAT) within a quasi-experimental design. The results show that the vast majority of parents of children who stutter perceive clearly negative communication attitudes in their children, while almost all parents of fluent children report no such difficulties. Statistical analysis (Student’s t-test) confirms a significant difference between groups, underscoring the impact of stuttering on parental perception and highlighting the need to systematically involve caregivers in diagnosis and therapy as well as to provide them with evidence-based education and support.